Highly Stretchable and Compressible Carbon Nanofiber–Polymer Hydrogel Strain Sensor for Human Motion Detection. Issue 3 (24th February 2020) - Cheng, Baowei; Chang, Shulong; Li, Hui; Li, Yunxing; Shen, Weixia; Shang, Yuanyuan; Cao, Anyuan
Abstract: With the development of technology and the improvement of living standards, wearable electronic devices have attracted more attention. Here, both stretchable and compressible hydrogel strain sensors based on carbon nanofiber powder (CFP) and polyvinyl alcohol (PVA) are prepared by freezing–thawing cycles. The PVA/CFP hydrogel exhibits excellent stretchable (366%) and compressible strains (70%). During 1000 loading–unloading cycles, the PVA/CFP hydrogel has a low plastic deformation (<10%, for both stretching and compressing), small energy loss efficiency (5.62% under stretching and 12.13% under compressing), and stable mechanical strength and excellent sensitivity, at conditions whether it is stretched to 100% or compressed to 50% strains. The stretchable and compressible PVA/CFP hydrogel can not only accurately detect multiple stretching behaviors of human activity, such as bending of joints, swallowing or breathing, but also detect the changes of pressure during walking. Besides, the PVA/CFP hydrogel can operate electronic screens due to its internal ions, with more potential application in soft robotics and electronic skin. Abstract : A polyvinyl alcohol/carbon nanofiber powder hydrogel fabricated by freezing–thawing cycles exhibits excellent stretchable strains (366%), compressible strains (70%), and satisfactory elasticity. Furthermore, it shows stable mechanical properties and excellent sensitivity, whether it is stretched to 100% or compressed to 50%. Multiple human motions can be detected by the hydrogel, which shows more potential application in soft robotics and wearable flexible devices.